COMMUNITY SERVICE THROUGH STORYTELLING RUBRIC DEVELOPMENT TO STRENGTHEN ENGLISH PROFICIENCY IN STATE JUNIOR HIGH SCHOOLS IN SITUBONDO - Annisa Kurnia Asri; Diah Galuh Sarimbit (Faculty of Letters Universitas Abdurachman Saleh Situbondo, 2025)
Storytelling is an engaging activity that benefits both the audience and the storyteller. Through storytelling, students practice pronunciation, intonation, expression, gestures, and grammatical accuracy, while audiences develop their listening comprehension and gain new knowledge. To facilitate storytelling activities and strengthen students’ English proficiency, MGMP Bahasa Inggris and MKKS SMP Negeri Kabupaten Situbondo organized an English Storytelling Contest as part of the Englishphoria event. The contest featured participants from public junior high schools across the region. A key component of this program was the enhancement of the storytelling assessment rubric. The rubric was collaboratively developed and adapted from international standards (CEFR and Cambridge English), aiming to ensure a more objective, fair, and comprehensive evaluation of students’ performances. The event ran smoothly and demonstrated the importance of clear assessment criteria in educational competitions. It is expected that similar events and rubric-based assessments will continue to support English language learning and encourage daily English use among students in Situbondo.